Analisis Penerapan Akuntansi Aset Tetap Terhadap PSAK No.216 Pada PT. PLN (Persero) Unit Layanan Pelanggan Medan Timur - Desy Ulina Manurung; Hendrik E.S Samosir; Magdalena J.Siringo Ringo (Jurnal Minfo Polgan, 2025)
This study aims to determine whether the implementation of fixed asset accounting at PT PLN (Persero) Customer Service Unit (ULP) Medan Timur complies with PSAK No. 216. The research applies a descriptive qualitative method, with data collected through interviews, observations, and documentation. The findings indicate that fixed assets are recognized at acquisition cost, including purchase price and all expenses incurred until the asset is ready for use, and recorded after the issuance of the Handover Report (BASTB/BASTP). Subsequent measurement adopts the cost model with the straight-line depreciation method. Post-acquisition expenditures are classified into capital expenditures, which are capitalized, and revenue expenditures, which are directly expensed. Derecognition of assets occurs when assets are disposed of, donated, or no longer provide economic benefits, while presentation and disclosure are based on book value in the financial statements. These findings support Suwardani et al. (2018), who concluded that PLN in North Sumatra generally complied with PSAK, and contrast with Bakri & Adriani (2020), who found that PLN Makassar Selatan still applied the declining balance method. Therefore, it can be concluded that PT PLN (Persero) ULP Medan Timur has implemented fixed asset accounting in accordance with PSAK No. 216.